2020
DOI: 10.1136/neurintsurg-2020-016165
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up outcomes of intracranial aneurysms treated using braided or laser-cut stents with closed-cell design: a propensity score-matched case-controlled comparison

Abstract: BackgroundThe impact of various stents on patients with intracranial aneurysms who undergo stent-assisted coiling has been debated. We conducted this study to compare follow-up outcomes of coiling procedures involving braided or laser-cut stents with closed-cell design. A propensity score-matched case-controlled analysis was applied.MethodsA total of 413 intracranial aneurysms consecutively coiled using laser-cut (n=245) or braided stents (n=168) in procedures performed between September 2012 and June 2017 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…In another study, the rate of aneurysm recanalization was lower in patients using braided stents than in those using laser-cut closed design stents. 35 In the present study, the initial (70%) and follow-up (71.4%) RR1 occlusion rates were acceptable, considering the findings of previous studies. At follow-up, recanalization was observed in three patients (14.3%; two with basilar top aneurysm and one with middle cerebral artery aneurysm).…”
Section: Discussionsupporting
confidence: 77%
“…In another study, the rate of aneurysm recanalization was lower in patients using braided stents than in those using laser-cut closed design stents. 35 In the present study, the initial (70%) and follow-up (71.4%) RR1 occlusion rates were acceptable, considering the findings of previous studies. At follow-up, recanalization was observed in three patients (14.3%; two with basilar top aneurysm and one with middle cerebral artery aneurysm).…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, a recent systematic review showed that the follow-up complete occlusion and recurrence in the LVIS group were comparable with the laser-cut group ( P = 0.454, 0.056, respectively) ( 26 ). Lim et al ( 35 ) reported a cohort study and demonstrated similar outcomes in follow-up and recurrence rates between the LVIS group and the Enterprise group. Our cohort study showed that for ruptured tiny intracranial aneurysms, patients treated with LVIS yielded significantly higher follow-up complete occlusion and lower recurrence rates ( P = 0.014), while the retreatment rate was lower without statistical significance ( P = 0.27).…”
Section: Discussionmentioning
confidence: 79%
“…Ge et al reported a higher rate of recanalization associated with enterprise stent than with the LVIS stent (10.7 vs 2.8%) ( 25 ). Lim et al observed in SAC of IAs, laser- cut and braided stent groups produced similar outcomes in follow-up, the difference of recanalization incidence rates between the braided- stent and the laser-cut group was not statistically significant ( 5 ).…”
Section: Discussionmentioning
confidence: 88%
“…Self-expanding braided stents have greater metal surface coverage and provide greater flow diversion to promote aneurysmal occlusion; examples include LVIS (Microvention, Aliso Viejo, CA, USA), LVIS Jr (Microvention), and LEO Baby (Balt, Montmorency, France). Both stent types are widely used in IA management and type superiority has not been established ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%